Mao. 12 - Takahashi, Rumiko, 1957-; Garrity, Shaenon K. (Shōnen Sandē komikkusu., 2023)
"When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way! Our friends ponder if past abuse explains or justifies bad behavior in the present. A battle against Renji and Mei raises another conundrum--is Nanoka's sword, Akanemaru, an asset or a liability? Then, two young thieves are pulled into a mysterious bag by a disembodied hand! Is it the last body part Natsuno has been searching for? Plus, the return of Byoki the cat demon..."--Back cover.